PENGEMBANGAN APPLICATION MANAGEMENT SYSTEM PADA WEBSITE JURUSAN ILMU KOMPUTER - Muhammad Donny Fadillah; Didik Kurniawan; Anie Rose Irawati (Jurnal Komputasi, 2016)
Most of the system or results of application the final project and computer thesis of science students that is creating applications that can help the performance of the Department. However, applications made have not been utilized properly, only presented and stored in the library only. Besides, container or a place to attach the application provided are difficult for users because there are settings for connecting to the ftp server. This study built an Application Management System (AMS) as one of the solutions that can be implemented to overcome these problems.AMS is a software used to organize the content. AMS facilitates the application that will be displayed as content on the main website. Implementation AMS of the content on the website using PHP programming language and MySQL database. The test results using Equivalence Partitioning (EP) shows that the AMS has been built to facilitate the user in posting applications. Applications that are embedded into websites using AMS can be run properly.Keywords: application management system, equivalence partitioning, website.